The elephant in the room: Intimate partner violence, women, and traumatic brain injury in sub-Saharan Africa - Anto-Ocrah, Martina; Aboagye, Richard Gyan; Hasman, Linda; Ghanem, Ali; Owusu-Agyei, Seth; Buranosky, Raquel (Frontiers in Neurology, 2022)
Background Intimate partner violence (IPV) is a gendered form of violence that has been linked with traumatic brain injury (TBI). The prevalence of IPV in sub-Saharan Africa (SSA) is estimated to be one of the highest globally. Yet, little is known about the association between IPV and TBI in the SSA context. In this scoping review, we examine the intersection between IPV and TBI in SSA to identify gaps, as well as intervention opportunities. Methods Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses—Extension for Scoping Review (PRISMA-ScR) guidelines to guide our analyses and reporting, we searched for published articles indexed in the four largest and most comprehensive library databases: Pubmed, Embase, Web of Science and PsychInfo. Given the increasing attention that has been placed on gender disparities and health in recent years, we focused on studies published between 2010 and 2021. Results Our search yielded 5,947 articles and 1,258 were IPV and SSA related. Out of this, only ten examined the intersection between IPV and TBI. All focused on outcomes in female populations from South Africa (n = 5), Ghana (n = 3), Uganda (n = 1), and Cameroon (n = 1). They were a mix of qualitative studies (n = 3), neuro-imaging/biomarker studies (n = 3), case studies/reports (n = 2), quantitative surveys (n = 1) and mixed qualitative/quantitative study (n = 1). Six studies evaluated subjective reporting of IPV-induced TBI symptoms such as headaches, sleep disruptions, and ophthalmic injuries. Three examined objective assessments and included Hypothalamic-Pituitary-Adrenal (HPA) dysregulation detected by salivary cortisol levels, magnetic resonance imaging (MRI) including diffusion tensor imaging (DTI) to evaluate brain connectivity and white matter changes. One final study took a forensic anthropology lens to document an autopsy case report of IPV-induced mortality due to physical head and face trauma. Conclusion Our findings demonstrate that both subjective and objective assessments of IPV and TBI are possible in “resource-limited” settings. The combination of these outcomes will be critical for viewing IPV through a clinical rather than a cultural lens, and for substantiating the assertion that gender, is indeed, a social determinant of brain health.